A Potential Role for a Genetic Variation of AKAP5 in Human Aggression and Anger Control - Richter, Sylvia; Gorny, Xenia; Marco-Pallares, Josep; Krämer, Ulrike M.; Machts, Judith; Barman, Adriana; Bernstein, Hans-Gert; Schüle, Rebecca; Schoels, Ludger; Rodriguez-Fornells, Antoni; Reissner, Carsten; Wüstenberg, Torsten; et al. (Frontiers in Human Neuroscience, 2011)
The A-kinase-anchoring protein 5 (AKAP5), a post-synaptic multi-adaptor molecule that binds G-protein-coupled receptors (GPCRs) and intracellular signaling molecules has been implicated in emotional processing in rodents, but its role in human emotion and behavior is up to now still not quite clear. Here, we report an association of individual differences in aggressive behavior and anger expression with a functional genetic polymorphism (Pro100Leu) in the human AKAP5 gene. Among a cohort of 527 young, healthy individuals, carriers of the less common Leu allele (15.6% allele frequency) scored significantly lower in the physical aggression domain of the Buss and Perry Aggression Questionnaire (BPAQ) and higher in the anger control dimension of the State-Trait Anger Expression Inventory (STAXI). In a functional magnetic resonance imaging (fMRI) experiment we could further demonstrate that AKAP5 Pro100Leu modulates the interaction of negative emotional processing and executive functions. To investigate implicit control-processes of anger control, we used the well-known flanker-task in order to evoke processes of action-monitoring and error-processing and added task-irrelevant neutral or angry faces in the background of the flanker stimuli. In line with our predictions, Leu carriers showed increased activation of the anterior cingulate cortex (ACC) during emotional interference, which in turn predicted shorter reaction times and might be related to stronger control of emotional interference. Conversely, Pro homozygotes exhibited increased orbitofrontal cortex (OFC) activation during emotional interference, with no behavioral advantage. Immunohistochemistry revealed AKAP5 expression in the human ACC and OFC. Our results suggest that AKAP5 Pro100Leu contributes to individual differences in human aggression and anger. Further research is warranted to explore the detailed role of AKAP5 in human emotional processing.